Stereotactic central/core ablative radiation therapy: results of a phase I study of a novel strategy to treat bulky tumor - Yang, Jun; Lu, Qiuxia; Qi, Weihua; Kolb, Ryann D.; Wang, Lei; Li, Yuan; Li, Sida; Lin, Yihui; Liu, Jiayi; Mourad, Waleed; MirkhaghaniHaghighi, Farzaneh; Slavisa, Tubin; et al. (Frontiers in Oncology, 2024)
Purpose: Bulky bulky tumor remains as a challenge to surgery, chemotherapy and conventional radiation therapy. We designed a novel therapeutic paradigm via strategy of Stereotactic Central/Core Ablative Radiation Therapy (SCART), which is based on the principles of SBRT (stereotactic body radiation therapy and spatially fractionated radiation therapy (SFRT). We intend to safely deliver an ablative dose to the core of the tumor and with a low dose at tumor edge. The purpose of the phase 1 study was to determine dose-limiting toxicities (DLT)s and the Maximum Tolerated Dose (MTD) of SCART. Methods and Materials: We defined a SCART-plan volume inside the tumor, which is proportional to the dimension of tumor. VMAT/Cyberknife technique was adopted. Patients with biopsy proven recurrent or metastatic bulky cancers were enrolled. The five dose levels were 15 Gy X1, 15Gy X3, 18GyX3, 21GyX3 and 24GyX3, while keeping the whole tumor GTV's border dose at 5Gy each fraction. Results: 21 patients were enrolled and underwent SCART. All 21 patients have eligible data for study follow-up. Radiotherapy was well tolerated with all treatment completed as scheduled. The dose was escalated for two patients to 24GyX3. No grade 3 or higher toxicity was observed in any of the enrolled patients. The average age of patients was 66 years (range: 14-85) and 13 (62%) patients were male. The median SCART dose was 18Gy (range: 15 -24). Six out of the 18 patients with data for overall survival (OS) died, and the median time to death was 16.3 months (range: 1 -25.6). The mean percent change for tumor shrinkage between first visit volumes andpost-SCART volumes was 49.5% (SD: 40.89, p-value:0.009). Conclusion: SCART was safely dose-escalated to 24 GyX 3 fractions, which is the maximum Tolerated Dose (MTD) for SCART. This regimen will be used in future phase II trials.